Effect of oral erythromycin in the treatment of preterm infants with feeding intolerance - Yasser Abdel Rahman Ahmed; Yasser Tolba Kassem; Eman Atia Abdel Rahman (Wolters Kluwer Medknow Publications, 2020)
Background It usually takes several days or even weeks to establish full enteral feeding (FEF) in preterm infants because of feeding intolerance (FI) related to gastrointestinal hypomotility. Clinical trials on prokinetic agents in preterm neonates, especially erythromycin, have reported conflicting results. There are limited data on prokinetic effect of erythromycin in preterm infants. Objective The authors aimed to evaluate the effect of oral administration of erythromycin in the treatment of preterm infants born at 30 weeks of gestation or more. Patients and methods A clinical trial was conducted on 60 preterm neonates born equal or more than 30 weeks of gestational age and admitted to the neonatal ICU at Kafr El-Shiekh General Hospital. Infants with FI were randomly divided into two groups: group A received oral erythromycin and group B did not receive treatment with erythromycin. Time to achieve FEF was considered as a primary outcome measure. Duration of parenteral nutrition (PN) expressed in number of days; number of days that feeds were withheld owing to FI; and duration of hospitalization were the other outcomes. Results Erythromycin group attained FEF earlier than the group without treatment with erythromycin. Therefore, PN duration was shorter in erythromycin group than the group without treatment. Moreover, the duration of hospitalization was shorter in erythromycin group than the other group. Conclusion This data suggest that oral erythromycin effectively reduces the time required to reach FEF, duration of PN, and length of hospital stay in stable preterm infants.